Pengembangan Konseling Behavioral Teknik Penguatan Positif Untuk Meningkatkan Self Order Siswa SMA - Ni Luh Dewi Cempaka Lata; Nyoman Dantes; I Ketut Dharsana (Jurnal Bimbingan dan Konseling Indonesia, 2022)
This research aimed at developing and testing test the acceptability and effectiveness of the implementation of a guidebook based on behavioral counseling theory with positive reinforcement techniques to increase self- order of high school students'. This study is research and development, which used the development model of 4D. This study involved 5 counseling guidance experts/practitioners, which consists of 3 Counseling Guidance lecturers at the Undiksha Faculty of Education and 2 High School Counseling Guidance Teachers. These experts aimed at testing the contents of this guidebook validity. The method used in analyzing the data is the Content Validity Ratio (CVR) from Lawshe. Meanwhile, to test the acceptability of this manual, the researcher involved 10 high school BK teachers as assessors. To test the effectiveness of involving 15 students in intact groups as test subjects for the effectiveness of the developed guidebook. Based on the 22 items of instruments used to assess content validity (CVI), it revealed a good validity for each item. The acceptance test of the manual shows a scale value of 3.79 and has a B (Good) score. Hypothesis testing shows that the guidebook is based on behavioral counseling theory of positive reinforcement techniques to increase students' self-order with t count 15,839 with a significance level of 0.05 and an ES value = 3.801 which is included in the High ES category. Abstrak: Penelitian ini bertujuan untuk mengembangkan dan menguji uji akseptabilitas dan efektivitas penerapan buku panduan berbasis teori konseling perilaku dengan teknik penguatan positif untuk meningkatkan keteraturan diri siswa SMA. Penelitian ini merupakan penelitian dan pengembangan yang menggunakan model pengembangan 4D. Penelitian ini melibatkan 5 orang ahli/praktisi BK, yang terdiri dari 3 orang dosen BK FK Undiksha dan 2 orang Guru BK SMA. Para ahli ini bertujuan untuk menguji validitas isi buku pedoman ini. Metode yang digunakan dalam menganalisis data adalah Content Validity Ratio (CVR) dari Lawshe. Sedangkan untuk menguji akseptabilitas manual ini, peneliti melibatkan 10 orang guru BK SMA sebagai asesor. Untuk menguji keefektifan dengan melibatkan 15 siswa dalam kelompok utuh sebagai subjek uji keefektifan buku panduan yang dikembangkan. Berdasarkan 22 item instrumen yang digunakan untuk menilai validitas isi (CVI), didapatkan validitas yang baik untuk setiap item. Tes penerimaan manual menunjukkan nilai skala 3,79 dan memiliki skor B (Baik). Pengujian hipotesis menunjukkan bahwa buku pedoman berbasis teori konseling perilaku teknik penguatan positif untuk meningkatkan keteraturan diri siswa dengan t hitung 15.839 dengan taraf signifikansi 0,05 dan nilai ES = 3,801 yang termasuk dalam kategori ES Tinggi.